Pelatihan Destinasi Wisata Bersih Melalui Teknologi Media Digital Dalam Menun-jang Pariwisata Desa Cipta Karya - Yuliana Yuliana; Shanti Veronica Br Siahaan; Petrus Benny (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: Cipta Karya Village is located in Bengkayang Regency, a small village that has interesting natural attractions for tourist visits. But there is still minimal awareness of visitors who are responsible for waste. Therefore, a community service program was held to manage waste into new goods so as to produce products to increase the economy of rural communities by utilizing digital media technology as a means of tourism promotion. This service aims to provide clean tourism education through waste management programs into new goods, counseling about (content) upgrades, and social media accounts as well as technical training in compiling promotional content based on digital media technology. The method of community service activities applied Socialization and discussion, training and mentoring, and evaluation, through evaluation aims to see the process of training activities in the long term by looking at the number of partner group participants when managing tourism. The results obtained in this service are increasing the insight of the village community about the use of waste in new goods. Visitors' concern for the tourist destinations visited and the use of digital media, namely the creation of clean tourism content to be published on the YouTube channel.      Keywords: digital media; net travel; tourist